(untitled) (Ghana Journal of Science, Technology and Development, 2022)
Host plant resistance in sweet potato, under a long-term management approach, is one of the most effective, economical, and environmentally benign management approaches for sweet potato virus diseases (SPVD). In the current study, different sweet potato genotypes were evaluated for resistance to the SPDV and also with higher yield potential under field conditions. The experiment was conducted from July – November 2018 at the University for Development Studies (UDS) experimental field. Thirty-two sweet potato genotypes, including five, already released varieties (also served as checks) were used. The genotypes (treatments) were arranged in a Randomized Complete Block Design (RCBD) with three plications. The results showed that three of the checks (Apomuden, Bohye, Tu-Purple) and PG17207-N1, PG17257-N1, PG17305-and N had significantly higher virus susceptibility levels as compared to the remaining genotypes. Thirteen (13) genotypes showed no visible symptom of the virus, fifteen (15) genotypes were moderately resistant to the disease whiles the remaining four (4) were slightly susceptible to the disease. The results further revealed that PG17584-N1, PG17257-N1 and PG17149-N2 produced the highest root yield while the least was observed for PG17205-N. PG17584-N1, PG17257-N1. Furthermore, PG17149-N2 combines higher root yield with resistance to the SPVD. They can therefore be used as resistant sources for further breeding interventions.